Research on Forwarding Performance for Network Function Virtualization - Hong Tang; Liang Ou (Dianxin kexue)
The key affecting factors of forwarding performance for NFV scenario were discussed, after parts of open source technologies on forwarding performance optimization were introduced briefly. An integrated NFV system end-end optimization scheme was put forward by means of serial open source software suite. Moreover, experiment reached to evaluate DPDK technology in single server case was did. It shows a remarkable increase on forwarding performance in single server achieved by open source suite. Studies provide a valuable reference NFV system design for both SDN appliance developer and network operators.